Fiscal Systems for Oil : The Government "Take" and Competition for Exploration Investment - Khelil, Chakib (World Bank, Washington, DC, 2012)
Exploration for petroleum occurs on the basis of government-granted concessions, leases, or contracts whose terms and conditions are established by law or negotiated case by case. An important part of these arrangements is the fiscal terms and conditions-bonuses, rentals, royalties, and taxes. The author looks at fiscal systems around the world and draws some conclusions about how governments compete for exploration investment.